Post-BPPV Syndrome: Our Experience in a Specialized Neurotology Clinic in Kolkata - Biswas, Anirban; Dutta, Nilotpal (Annals of Otology and Neurotology, 2019)
Introduction The common cause of approximately 25 to 30% of all patients presenting to the neurotologist with the complaint of head-spinning is benign paroxysmal positional vertigo (BPPV) that is the commonest cause for which a patient attends a vertigo clinic. Though BPPV is very effectively treated with the canalith repositioning maneuver (CRM), a considerable percent of these patients (34–61% as per different studies)78910 is not completely symptom-free even after a very successful maneuver (s) and complain of a new set of symptoms of light-headedness, unsteadiness, or dizziness or a combination of them termed as post-BPPV syndrome or as residual dizziness (RD) after successful correction of BPPV. Post-BPPV syndrome induces a very poor quality of life and is very incapacitating to most patients who suffer from it.Materials and Methods In Vertigo and Deafness Clinic, Kolkata, a total number of 200 patients were diagnosed with geotropic variety of BPPV in a period of 1 year from April 1, 2018 to March 31, 2019. Out of these 200 patients, the study was conducted on 178 patients who came for follow-up and also underwent all the necessary vestibular function tests. The remaining 22 patients who did not turn up for follow-up or did not undergo the tests either due to financial constraints or lack of time were excluded from the study group. The study was limited only to patients who had geotropic nystagmus and in patients with ageotropic nystagmus who were excluded from the study. One hundred seventy-eight patients of BPPV who were included in the study were managed by a protocol elaborated below devised by the first author.Results Following this protocol of BPPV management, only 23 (13%) patients after successful CRM presented with post-BPPV syndrome that is much less than the international figures of 34 to 61%. Analysis of data also showed that there was a huge psychic component in post-BPPV syndrome and that there was practically no organic vestibular deficit in post-BPPV syndrome.Conclusion Following our protocol of management of BPPV patients, which does not involve any new maneuver, only 13% of the patients complained of RD after the successful repositioning maneuvers. This is far lesser than the published international figures and this protocol may hence be tried and followed by other neurotology centers too. This protocol drastically reduces the morbidity of patients after the BPPV has been corrected by the requisite maneuvers. In our group of 23 patients who had post-BPPV syndrome out of 178 patients who had BPPV, the symptoms subsided spontaneously without medication within 3 weeks in more than 70% of patients. Only in three (13%) patients of post-BPPV syndrome, the RD persisted up to 12 weeks where drugs (selective serotonin reuptake inhibitor, benzodiazepines) and professional psychological counseling were required. None of these patients required any vestibular sedatives or the so called antivertigo drugs for amelioration of symptoms. It may hence be concluded that management of BPPV by this protocol reduces the incidence of post-BPPV syndrome and that antivertigo drugs have no role in the management of post-BPPV syndrome.
Keywords: post BPPV; residual dizziness; light headedness; unsteadiness; Canalith repositioning Manoeuvre